Can iFOBT (immunochemical faecal occult blood test) for bowel cancer screening be safely deferred for five years after a colonoscopy?. (2020) - Khaing, Myat Myat; Lin, Lei; Rahman, Tony; Peter-Kini, Geogry; Croese, John; Hodgson, Ruth
No abstract available